Efektivitas Kebijakan Bantuan Sosial dalam Menanggulangi Kemiskinan di Indonesia - Halizatunnisa, Siti Shafa; Safitri, Rika; Asysyabani, Qoorie Handayani; Ramadhani, Fajwah Rahma; Iswandini, Adinda Putri; Nabil, Bagas; Kaliky, Viqram Januar Gawi; Herdiana, Dian (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Poverty is one of the main problems faced by Indonesia. Bansos or social assistance is assistance provided by the government and other institutions aimed at vulnerable and poor communities. This study uses a qualitative descriptive approach by utilizing data from the APBN, the Central Statistics Agency (BPS), and official ministry reports as the main sources. Data collection was carried out through document studies and interviews, while data analysis was carried out using a comparative analysis approach to compare the effectiveness of social assistance policies in various contexts. The purpose of writing this article is to analyze the effectiveness of social assistance, as well as to evaluate bansos in overcoming poverty in Indonesia. Overall, social assistance (bansos) plays an important role in reducing poverty levels in Indonesia, but also has an impact on increasing the country's fiscal burden. Therefore, social assistance policy reform must focus on increasing efficiency, strengthening the management system, and controlling the fiscal burden so that this policy is not only temporary.